Haemato-Biochemical Alterations in Dogs with Vomition - Khanduri, Rimjhim; Raval, Sunant K.; Dave, Keshank; Rao, Neha (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Vomition is a common clinical presentation in small animal practice and may be associated with gastrointestinal and systemic diseases.Fifty cases of vomition in dogs were studied at Veterinary Clinical Complex of the College in Anand during the period of six months forclinical and haemato-biochemical alterations in comparison to 8 normal healthy dogs. Among 50 dogs, the incidence of vomiting possiblydue to Parvo viral infection, pyometra, renal disorders, encylostoma infection, pseudo-pregnancy, hepatic disorders, thrombocytopenia,neutrophilia and dietary abnormalities was in 44.0, 2.0, 14.0, 14.0, 2.0, 4.0, 2.0, 14.0 and 4.0 % cases, respectively. The levels of PCV, TLCand basophils were increased significantly (p
Keywords: Clinical signs; Dog; Haematology; Serum biochemistry; Vomition.